2010
DOI: 10.1111/j.1574-6941.2010.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Community characterization of anaerobic methyltert-butyl ether (MTBE)-degrading enrichment cultures

Abstract: Use of the fuel oxygenate methyl tert-butyl ether (MTBE) has led to widespread environmental contamination. Anaerobic biodegradation of MTBE observed under different redox conditions is a potential means for remediation of contaminated aquifers; however, no responsible microorganisms have been identified as yet. We analyzed the bacterial communities in anaerobic-enriched cultures originating from three different contaminated sediments that have retained MTBE-degrading activity for over a decade. MTBE was trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…If anaerobic biodegradation occurs, MTBE is usually transformed to TBA, which often persists (Somsamak et al, 2006). Acetogenic bacteria, members of methanogenic food webs, are hypothesized to be responsible for ether cleavage of the MTBE molecule and use the released methyl group as a carbon source; however, the pathway and particular organisms responsible are yet to be defined (Youngster et al, 2010a; Youngster et al, 2010b). Field experiments at VAFB have shown that MTBE transforms to TBA under strongly anaerobic conditions induced by experimental ethanol addition (Mackay et al, 2007; McKelvie et al, 2007), with an estimated pseudo-first-order reaction rate constant of 0.046 day −1 (after a lag period of about two months).…”
Section: Biodegradation Of Mtbe and Tbamentioning
confidence: 99%
“…If anaerobic biodegradation occurs, MTBE is usually transformed to TBA, which often persists (Somsamak et al, 2006). Acetogenic bacteria, members of methanogenic food webs, are hypothesized to be responsible for ether cleavage of the MTBE molecule and use the released methyl group as a carbon source; however, the pathway and particular organisms responsible are yet to be defined (Youngster et al, 2010a; Youngster et al, 2010b). Field experiments at VAFB have shown that MTBE transforms to TBA under strongly anaerobic conditions induced by experimental ethanol addition (Mackay et al, 2007; McKelvie et al, 2007), with an estimated pseudo-first-order reaction rate constant of 0.046 day −1 (after a lag period of about two months).…”
Section: Biodegradation Of Mtbe and Tbamentioning
confidence: 99%
“…MtBE concentrations decreased strongly in all monitoring wells from 2009 to 2015. The detection of TBA in almost all monitoring wells in 2013 indicates that demethylation is the first step in the MtBE biodegradation in the aquifer (Youngster et al 2010 ). Fractionation of stable carbon isotopes of MtBE and TBA in groundwater in 2009 and 2013 confirmed degradation of MtBE.…”
Section: Discussionmentioning
confidence: 99%
“…Kw12) (22.8%) also belonging to the phylum Firmicutes (60). Similarly, following continual enrichment of an anaerobic MTBE-degrading consortium, researchers reduced the community to three dominant phylotypes belonging to Deltaproteobacteria, Chloroflexi, and Firmicutes (67). In addition, Clostridia were found in anaerobic MTBE-degrading consortia under sulfate-and iron-reducing conditions (44).…”
Section: Figmentioning
confidence: 97%
“…The cultures were maintained with anthroquinone-2,6-disulfonate (AQDS), sulfate, or fumarate as electron acceptors, and the authors found that the microbial diversity varied under these different conditions. In another recent study, other researchers characterized the community composition of anaerobic enrichment cultures originating from three different contaminated sediments (67). Interestingly, terminal restriction fragment length polymorphism (TRFLP) profiles indicated substantially different community profiles from MTBE-degrading microcosms established from different sediment sources.…”
mentioning
confidence: 99%